Discharge against medical advice (DAMA): Causes and predictors - Ashrafi, Ensieh (Electron Physician, 2017)
BACKGROUND AND AIM: DAMA is a result of patient dissatisfaction, which increases the rate of readmission, mortality, and complications. In this study, the causes and predictors of DAMA in Shahid Labbafinejad Hospital of Tehran were determined. METHODS: The descriptive and analytical study was conducted in 2016 from the information of 1,168 hospitalized patients in the period of 2015 and the first half of 2016. Patients’ information was collected using checklists and through clinical records, nursing unit reports, and telephone calls. The collected data were analyzed using SPSS-v18 software and by employing chi-square test and logistic regression modeling. RESULTS: The DAMA rate was estimated at 3.27%. Among the causes of DAMA, the high rates were related to personal problems (39.04%) and going to other centers (34.93%), and the lowest level was related to dissatisfaction with the physician (3.08%). Age groups (19–37, OR=2.17), (38–56 years, OR=1.70), and (57–75, OR=1.62), gender (male, OR=1.47), locations (Tehran city, OR=0.61) and (Tehran Province, OR=0.63) were predictors of DAMA (p<0.05). CONCLUSIONS: The importance of DAMA requires practical measures such as creating a suitable environment for patients, providing consulting services for youth, improving staff relations, providing assistance for patients in need, and removing accommodation problems of patients and their companions to reduce the DAMA.